Analysis Redox Reaction on Zinc-Coating Thickness Test in Metal Processing Industry of Small and Medium Enterprises - Gatot Triyanto; Ricky R. Saputro; Chepi Reynaldir; Khoirudin Khoirudin; Sukarman Sukarman (Jurnal Akademika Kimia, 2022)
This study discusses the implementation of redox reactions on the thickness test of the galvanized (zinc-coated) layer using the JIS-H-0401 standard to help Small and Medium Enterprises (SMEs) industries. Some of the finished products go through the galvanizing process in the metal processing industry. Quality constraints, especially related to the thickness of the galvanic (zinc-coated) layer, have become an object that is less controlled because of the limitations of the test equipment used. This research uses an experimental method applied to one of its products: a flat washer with SPCC material and a thickness of about 2.20 mm. SPCC - SD material is classified as low carbon steel based on its carbon content. 5-unit flat washers were identified with sample codes A, B, C, D, and E. Flat washers have an internal diameter of 22.65 - 22.7 mm. In comparison, the outer diameter is between 43.75 - 43.80. The redox reaction process uses HCl (hydrochloric acid) with a concentration of 1 M, which is diluted with water (H2O). The zinc thickness test results show that the flat washer has an average thickness of 10.52 microns with a minimum and maximum thickness variation of 10.66 -10.72 microns.